2017
DOI: 10.4236/wjm.2017.78018
|View full text |Cite
|
Sign up to set email alerts
|

Stress Evaluation at the Maximum Strained State by EBSD and Several Residual Stress Measurements for Plastic Deformed Austenitic Stainless Steel

Abstract: This paper studies a method for obtaining the stress with plastic deformation by finding the plastic strain on U-bent specimens of austenitic stainless steel that have been subjected to large plastic deformation using the EBSD (Electron Backscatter Diffraction) method. The Mises stress calculated on the basis of the KAM of the EBSD shows good agreement with the stress that can be geometrically calculated from the U-bent specimens. In contrast, general methods for measuring residual stress on the basis of elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Figure 6(c) shows the grain boundaries of parent austenite grains and Figure 6(d) the inverse pole Figure of that austenite grain. Comparison between them shows that brighter parts of Figure 6(a) demonstrate lower stress level (blue parts) in Figure 6(b) which represent smaller distortion of tempered martensite [45]. In addition, although there are a few lathes of initial martensite in the structure, most of them are plate martensite and oriented along the grain boundaries of parent austenite grains (compare Figure 6(b,c)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6(c) shows the grain boundaries of parent austenite grains and Figure 6(d) the inverse pole Figure of that austenite grain. Comparison between them shows that brighter parts of Figure 6(a) demonstrate lower stress level (blue parts) in Figure 6(b) which represent smaller distortion of tempered martensite [45]. In addition, although there are a few lathes of initial martensite in the structure, most of them are plate martensite and oriented along the grain boundaries of parent austenite grains (compare Figure 6(b,c)).…”
Section: Resultsmentioning
confidence: 99%
“…It is clear in this picture (Figure 5) that initial martensite (bright red) is formed mostly as plate martensite. Figure 6 [45]. In addition, although there are a few lathes of initial martensite in the structure, most of them are plate martensite and oriented along the grain boundaries of parent austenite grains (compare Figure 6(b,c)).…”
Section: Electron Backscatter Diffraction (Ebsd)mentioning
confidence: 97%
“…[61][62][63] The Kikuchi patterns-based analysis of EBSD method enables the measurement of the stress variation by measuring the elastic strain, lattice rotation angle, and the geometrically necessary dislocation density. Sakakibara and Kubushiro [64] demonstrated that measurement of the kernal average misorientation through EBSD method can produce more accurate estimations of true Mises stress when the true strain is not less than 0.05. More recently, a novel characterization method, namely, Bragg edge neutron imaging method, was proposed by Morgano et al [65] With this method, it is assumed that the lattice strain can be more efficiently characterized when the spatial resolution of conventional nondestructive methods reaches the limit.…”
Section: Measurement Of Residual Stressesmentioning
confidence: 99%
“…[21][22][23] Sakakibara and Kubushiro reported a linear relationship between the average KAM and measured true strain up to 0.18 in austenitic steel. [24] Therefore, the KAM maps in Figure 2c illustrate various local plastic strains. Confidence index (CI) lower than 0.1°was removed from the KAM maps.…”
Section: Microstructure Evolution and Strain Distribution Near The Fr...mentioning
confidence: 99%